Vertical Pay Dispersion, Peer Observability, and Misreporting in a Participative Budgeting Setting - Guo, Lan; Libby, Theresa; Liu, Xiaotao (Kelvin); Tian, Yu (Contemporary Accounting Research, 2020)
ABSTRACT In this study, we examine the joint effect of vertical pay dispersion and peer observability on subordinates' misreporting choices. We adopt a participative budgeting setting in which two subordinates report to one superior, and we manipulate vertical pay dispersion (low/high) and peer observability (absent/present). Subordinates have private information about actual project costs and can over‐report project costs to the superior without detection and thus create budgetary slack. When a peer's reporting choices are observable, we predict and find that peer reporting choices have an asymmetric influence on the focal subordinates' reporting choices, and this asymmetric influence depends on the level of vertical pay dispersion. Specifically, we find that when vertical pay dispersion is low, subordinates who observe peer reports containing low slack misreport less , whereas observing peer reports that contain high slack has no significant effect. However, when vertical pay dispersion is high , subordinates who observe peer reports containing high slack misreport more , whereas observing peer reports that contain low slack has no significant effect. Driven by these asymmetric effects, subordinates misreport less in the presence of peer observability than in its absence when vertical pay dispersion is low and misreport more in the presence of peer observability than in its absence when vertical pay dispersion is high. Overall, our findings suggest that when a firm has a more egalitarian pay structure (i.e., low vertical pay dispersion), an open information policy is conducive to a more honest reporting environment, whereas under a more hierarchical pay structure (i.e., high vertical pay dispersion), open information policies can compromise the honesty of subordinates' reports.